When R&D spending is not enough: The critical role of culture when you really want to innovate - Wang, Sheng; Guidice, Rebecca M.; Tansky, Judith W.; Wang, Zhong‐Ming (Human Resource Management, 2010)
AbstractOrganizations invest substantial resources in research and development (R&D) to increase long‐term performance. Despite these investments, contextual contingencies can impact innovation. Our findings show that Chinese manufacturers with cultures emphasizing innovation and teamwork more effectively use financial resources in the innovation process. Findings also demonstrate that the impact of education on innovation is greater with low stability and high teamwork and innovation orientations. Results also indicate that a culture emphasizing outcomes and stability leads to lower levels of innovation irrespective of financial and human resources invested. Finally, we found a negative curvilinear interaction between R&D spending and outcome orientation on innovation. © 2010 Wiley Periodicals, Inc.